Fisheries science and marine education catalyze the renaissance of traditional management (rahui) to improve an artisanal fishery in French Polynesia. (January 2021) - Filous, Alexander; Lennox, Robert J.; Beaury, Jean Pierre; Bagnis, Hinano; Mchugh, Mathew; Friedlander, Alan M.; Clua, Eric E.G.; Cooke, Steven J.; Fuller, Todd K.; Danylchuk, Andy J.
Abstract: Coral reef fisheries provide important ecosystem services to coastal communities, yet in the Pacific Islands, many of these contemporary fisheries are threatened by overexploitation. Historically, Pacific Island societies successfully utilized community-based management and spatial temporal closures to regulate the harvest of marine resources. In recognition of their past success these actions are currently being reemployed throughout the region. However, in many communities, innovative approaches may be needed to revitalize such practices and adapt traditional management to contemporary societal needs and expectations. This study presents the case of Anaa Atoll, a remote Pacific Island in the Tuamotu Archipelago of French Polynesia, and the community's efforts to conserve a culturally important but overexploited bonefish ( Albula glossodonta ) fishery. Ultimately, fisheries research, education, and the creation of Aire Marine Educative (a marine area that is managed by a local primary school) were successful in building social cohesion and supporting the renaissance of rahui (a traditional form of restricting access to resources and or territories) to manage this fishery. On March 1st, 2019, the community of Anaa reinitiated this tradition for the first time in centuries. Based on these experiences, and an ensuing increase in the Spawning Potential Ratio of the bonefish stock, it is proposed that nationally recognized local management systems that incorporate fisheries research, youth education, and the cultural practices of communities should be supported in the marine policies of the Pacific Islands and beyond. Highlights: Research and education supported the management of an Albula glossondonta fishery. An Aire Marine Educative was established where the stock is exploited. The Tavahiroa Elementary School petitioned the community to institute a rahui . The ensuing increase in SPR to 17% suggests the fishery is more sustainable. Marine policies should catalyze bottom up fisheries management with education.